2013
DOI: 10.1177/0081246313494154
|View full text |Cite
|
Sign up to set email alerts
|

The state of the psychological contract and employees’ intention to leave: The mediating role of employee well-being

Abstract: Changes in the work environment can influence employees' perception of the employment relationship, their psychological contracts, and consequently, their work-related attitudes and behaviour. The study aimed to demonstrate the mechanism through which the state of employees' psychological contract impacts employees' intention to leave employment and the role of employee well-being as a mediator. Cross-sectional data were obtained from employees representing various organisations (N = 246). Structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
5
14
0
1
Order By: Relevance
“…Studies of work-related stress have argued that breaches and violations of PC can make a significant contribution to the stress experienced by employees (Noblet et al 2009). PC fulfilment has been found to predict job and life satisfaction (De Cuyper et al 2011), resistance to change (Van de Heuvel and Schalk 2009); and the level of trust and fairness between employees and employers ( Van der Vaart et al 2015;Van der Vaart et al 2013). Organisations that fulfill employees' PC have low work-related anxiety and depression, and job insecurity (Guest et al 2010).…”
mentioning
confidence: 99%
“…Studies of work-related stress have argued that breaches and violations of PC can make a significant contribution to the stress experienced by employees (Noblet et al 2009). PC fulfilment has been found to predict job and life satisfaction (De Cuyper et al 2011), resistance to change (Van de Heuvel and Schalk 2009); and the level of trust and fairness between employees and employers ( Van der Vaart et al 2015;Van der Vaart et al 2013). Organisations that fulfill employees' PC have low work-related anxiety and depression, and job insecurity (Guest et al 2010).…”
mentioning
confidence: 99%
“…The literature states that endeavoring to fulfill PCF can help employers retain employees (Van der Vaart et al, 2013;van Stormbroek & Blomme, 2015) This study corroborated these findings. PCF was shown to be a significant positive predictor of engagement, in accordance with H2, and has a negative relationship with turnover intention, in accordance with H3.…”
Section: Pcfsupporting
confidence: 77%
“…Literature suggests that work -life balance is an issue that organizations have to manage carefully (Sturges & Guest, 2004), especially when immigrant or other minority employees are the focus of interest (Peeters & Oerlemans, 2009). Some authors state that too little consideration is given to the nature of work -life balance of immigrants, especially from Eastern European countries (Guest, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…When a person is unable to meet the demands of work and non-work domains, the conflict occurs. Previous research was focused on conflict between work and family roles, however recently it is emphasized that broader definition of the non-work area is required (Sturges & Guest, 2004). Guest (2002) suggested that new generation of workers with new values is emerging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation